The MADS-Box Transcription Factor ClAG2 Is a Key Regulator for the Formation of Double Flower in Clematis L. - Xuerong Chen; Ping Zhou; Nanhong Guo; Yiping Zheng; Xiumei Hou; Lihui Zeng (Horticulturae)
Flower morphology is a critical ornamental trait in flowering plants. Elucidating the molecular mechanisms underlying flower development is essential for the breeding of diverse ornamental plant cultivars. The ABCE model genes are pivotal in regulating floral development in angiosperms. In order to understand the molecular mechanism of flower development in Clematis, nine ABCE model genes were identified from the transcriptome data of Clematis cv. ‘Amethyst Beauty’. Quantitative real-time polymerase chain reaction (qRT-PCR) analysis revealed tissue-specific expression patterns among these genes. ClPI, ClSEP1, and ClSEP3 were predominantly expressed in sepals. ClAP3, ClPI, ClAG2, ClSEP1, and ClSEP3 were highly expressed in stamens. ClAG1 was exclusively expressed in pistils. These findings suggested that ABCE genes may play an important role in regulating the formation of flower morphology in the Clematis. The open reading frame (ORF) of ClAG2 was cloned and overexpression of ClAG2 in tobacco resulted in shorter corolla tube, reduced crown area, and stunted stamen. ClAG2 may have a negative effect on the formation of double-tepal flowers of Clematis and play a specific role in stamen and pistil development. Yeast two-hybrid assays demonstrated that ClAG2 could interact with class E proteins ClSEP3 and ClSEP4 but not with class B proteins ClAP3 and ClPI. Our results will lay a theoretical foundation for further research on the mechanism of flower development regulation in Clematis.